ANALISIS KERUSAKAN INERT GAS SYSTEM PADA SAAT BONGKAR MINYAK MENTAH MT. MARLIN 88 - Bayu Samudra, Rezky; Darmana, Eka (Majalah Ilmiah Gema Maritim, 2022)
MT. MARLIN 88 is a type of tanker loaded with crude oil, tankers with dead weight above 20,000 tons must be equipped with an Inert Gas System, there are obstacles related to damage to the Inert Gas System when unloading crude oil, the purpose of this study is to determine the cause of the occurrence of Inert Gas System malfunction in MT. MARLIN 88. The data collection method used is direct observation in the field on the ship MT. MARLIN 88, interviews with the crew responsible for the inert gas system, and literature studies from various literatures. From the data obtained, then an analysis was carried out using a qualitative descriptive analysis approach. The results of this study concluded that the damage to the inert gas system on the ship MT. MARLIN 88 possible cause is the maintenance of the inert gas system in MT. MARLIN 88, has not reached its maximum results due to damage to the Oxygen Analyzer which resulted in the supply of inert gas required for the cargo tank to be high in O2 content. This may be influenced by the lack of in-depth understanding of some of the crew on board the inert gas system